Wellness Tourism: Utilizing the Slopes of Mount Welirang for Forest Healing Based on Community-Based Tourism - Andhika Yudha Pratama; Daya Negri Wijaya; Dwi Wulandari; Annisya Annisya; Galang Putra Nusantara; Dini Putri Ratna Meritasari (International Journal of Science and Environment (IJSE), 2025)
This study is one of the studies that examines CBT as an approach to developing wellness tourism, the potential of the slopes of Mount Welirang that can be used for forest healing and marketing using the 5P concept (Product, Price, Place, Promotion, and People). The method used in this study is a qualitative method based on Community Based Tourism (CBT). Data collection was carried out using focus group discussion (FGD) techniques, interviews, observation, and documentation studies. Data analysis techniques used an interactive model on the application of Community Based Tourism (CBT) implemented in the development of forest healing on the slopes of Mount Welirang. The results of the study are as follows: 1) The development of forest healing with the application of Community-Based Tourism (CBT) is based on three pillars, namely community empowerment, ecological conservation, and sustainable community innovation. 2) The potential of the slopes of Mount Welirang lies in its geological and topographical foundations, biodiversity as natural medicine, amd sencory stimulation. 3) Marketing using the 5P concept. The main products offered are the development of forest healing destinations that include forest-based healing activities, integrated tourism packages, and educational added value. Price refers to a value-based pricing approach. Place focuses on the slopes of Mount Welirang as the main object. Promotion is carried out using a digital approach based on transformational narratives. People focuses on the community, which is at the center of the overall forest healing development on the slopes of Mount Welirang.